2021
DOI: 10.1016/j.heliyon.2021.e08072
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of personal innovativeness and driving experience on factors influencing adoption of BEVs in Malaysia: An integrated SEM–BSEM approach

Abstract: Electric cars are relatively in the early stage of acceptance in Malaysia, the purpose of the current research was to determine the factors affecting the adoption of battery electric vehicles in Kuala Lumpur, Malaysia. This research utilized a quantitative method to gather and analyze the data and proposed a novel theoretical framework to explain the acceptance of battery electric vehicles. 500 surveys were distributed and 322 were gathered. Respondents of the study were University lecturers, postgraduate stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 124 publications
1
17
0
Order By: Relevance
“…Few researchers used Rogers's (2003) diffusion of innovation theory (DoI) to study EV adoption behavior [26]. Khazaei and Tareq (2021) used an extended unified theory of acceptance and the use of technology (UTAUT2) model [27] to examine consumers' acceptance of electric vehicles in Malaysia [28].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Few researchers used Rogers's (2003) diffusion of innovation theory (DoI) to study EV adoption behavior [26]. Khazaei and Tareq (2021) used an extended unified theory of acceptance and the use of technology (UTAUT2) model [27] to examine consumers' acceptance of electric vehicles in Malaysia [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tu and Yang's (2019) research showed that subjective norms significantly impact EV purchase decisions [41]. Khazaei and Tareq's (2021) research in Malaysia showed that social approval is one of the important factors for consumers' adoption of battery electric vehicles [28]. Therefore, social influence may affect individuals' attitudes and intentions towards electric two-wheelers also as it is a new technology.…”
Section: Social Influencementioning
confidence: 99%
“…It is startling to see that most teenagers at the age of 18 years are highly sexually active, resulting in high teenage pregnancies [ 5 ]. As Malaysia rapidly urbanizes and industrializes, the new generation not only overcomes developmental obstacles but also be prepared to deal with a plethora of environmental problems and pressures [ 6 , 7 ]. Premature sexual activities among teenagers increase the risk of unprotected sex and various sex partners that may end up in sexual spread infections, such as the risk of premature rupture of membranes, acquired immunodeficiency syndrome (AIDS), postpartum infection [ 8 , 9 ], and preterm labor, which may influence their study and future.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The UTAUT theory has been used and extended by many researchers in the context of EVs adoption [80][81][82][83][84][85][86][87][88][89][90]. The adoption of EVs has been very limited, which is why the different researchers extended the UTAUT model to examine the factors which enhance the consumer behavior towards these sustainable vehicles.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Karunanayake and Samarasinghe [87] analyzed the perceived risk with the extension of UTAUT towards the purchase intention of EVs. Khazaei and Tareq [83] examined the UTAUT theory with the moderating effect of personal innovativeness and driving experience towards EV adoption. Another study by Khazaei [88] extended the UTAUT model with personal innovativeness and price value to examine the consumer intention to use EVs.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%